A Neonate with Subcutaneous Fat Necrosis after Passive Cooling: Does Polycythemia Have an Effect? - Erhan Calisici; Mehmet Yekta Oncel; Halil Degirmencioglu; Gonca Sandal; Fuat Emre Canpolat; Omer Erdeve; Serife Suna Oguz; Ugur Dilmen (Hindawi Limited, 2013)
Subcutaneous fat necrosis (SCFN) is an inflammatory disorder of adipose tissue. The main risk factors for the development of SCFN are perinatal asphyxia and hypothermia. Presented here is a case of a newborn who developed SCFN in association with polycythemia and hypocalcemia following treatment by passive cooling. Neonates who undergo passive or whole body cooling therapy should be closely monitored for any signs of SCFN.